Literature Review: The Effectiveness of the 5E Learning Cycle Model in Addressing Science Misconceptions among Elementary School Students - Novelina, Fryda; Rahmawati, Yuli; Utami, Nidya Chandra Muji (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
Misconceptions are one of the primary obstacles in learning science at the elementary school level, which can hinder in-depth understanding of concepts and disrupt the learning process, ultimately causing students to fail in their learning. This study aims to examine the role of the 5E Learning Cycle model (Engage, Explore, Explain, Elaborate, Evaluate) in overcoming misconceptions of science concepts among elementary school students through a literature review approach. The method used is a systematic literature review of various relevant scientific sources over the past ten years. The research findings indicate that the 5E Learning Cycle model is effective in identifying, clarifying, and reconstructing students' misconceptions through structured and student- centered learning stages. The "Engage" and "Explore" stages allow educators to reveal students' initial understanding, while the "Explain" and "Elaborate" stages support the reinforcement of correct scientific concepts. The "Evaluate" stage helps facilitate conceptual shifts in students. Based on the literature review, the 5E Learning Cycle model is recommended as an effective pedagogical approach to improving the quality of science concept understanding and reducing misconceptions among elementary school students.